KEPUASAN KERJA KARYAWAN PUBLIC AREA SECTION PADA HOTEL GRAND CENTRAL PEKANBARU - Chalid Aulia Benzani; Andri Sulistyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
This study was to determine the level of employee satisfaction in the public area section of Grand Central Hotel Pekanbaru. Implementation What factors are affecting the level of employee satisfaction in the public area section of Grand Central Hotel Pekanbaru. The research was aimed to know how public employee job satisfaction section area at Grand Central Pekanbaru.This study uses qualitative descriptive method to describe the problem in the management of the facility. Subjects used as many as eleven people as the key information.From the analysis it was found that the physical working environment and working environment versial physical non significant effect on employee performance pekanbaru grand central hotel.Keywords: Satisfaction, Amenities, Hotel.